DeGois - The Portuguese National Academic CV Platform - Pinto, Carlos Sousa (2017)
Science and Technology Foundation (FCT) is the Portuguese authority responsible for the management of science and technology that deals with a large part of governmental funds to be allocated to researchers, in terms of grants and research projects financing. FCT owns DeGois, a Portuguese academic CV platform derived from Lattes, the Brazilian system of curricula. Due to that, Deg6is inherited almost all the assumptions adopted for that platform without any alignment with the international recommendations or standards and best practices about usability in use today. This fact introduced several problems concerning the interoperability with other national and international systems and kept away many potential users. A consequence of this was the decision to develop a new version of DeGois, as part of the national project PTCRIS (Portuguese Current Research Information System). In this article we describe the path that led to the development of the new version of DeGois, highlighting the objectives, motivations, expectations, options, results, limitations and future work. (C) 2017 The Authors. Published by Elsevier B.V. This is an open access article under the CC BY -NC -ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).